Methodology of Literary Psychologism Analysis in University Classes (Eurasian Journal of Philology Science and Education, 2026)
The purpose of this article is to substantiate the methodology of literary psychologism analysis in higher education classes. The main areas of scientific research are the methodology of teaching literature at the university, the study of the epic work. The idea of ​​the scientific research - teaching students to analyze the means of psychologism in modern Kazakhstani literature is necessary for the development of their literary competencies.The scientific significance of this article is that its materials can be used to develop new strategies for analyzing literary works in higher education. The practical significance of the work is expressed in the fact that its materials and results can be used to compile methodological recommendations, write textbooks on the study of psychologism in works of fiction.The research methodology is based on an interdisciplinary approach to teaching students literature. The study relies on the materials and tools of literary criticism, pedagogy, methods of teaching literature, history. Various methods were used to reveal the topic of the article. The use of the theoretical research method allowed us to carry out a deep analysis of scientific literature on literary criticism, pedagogy, didactics, and methods of teaching literature. The use of the observation method ensured the effectiveness of innovative teaching of students to analyze psychologism in modern Kazakhstani literature.The developed methodology for analyzing literary psychologism is productive. The work solves the problems of studying literary works taking into account psychologism.Keywords: psychologism in fiction, modern Kazakhstani literature, methods for studying an epic work, interactive learning.